Student satisfaction through academic advising: How effective is the academic advisor? / Salina Hamed, Faridah Hussin and Sarina Md Jam - Hamed, Salina; Hussin, Faridah (Universiti Teknologi MARA, Pulau Pinang & Pusat Penerbitan Universiti (UPENA), 2015)
The academic advising involves helping students to understand the paths that could be taken so that students can draw their own roadmaps to achieve their goals and monitor their own progress. Moreover, the academic advising has become an integral part of the learning culture in the university. As we know, life in the university can be a very challengeable experience especially for the new students. Hence, the academic advisors can ease the students’ transition from school life to the university life by providing them with useful information about knowledge and services as well as guidance for students throughout their entire education experiences. Furthermore, the academic advising services will enhance students’ greater satisfaction with their academic experience, better self-understanding and a sense of success in the achievement of personal and academic goals. In view of this, this survey was carried out to determine the style of advising used by the current academic advisor, the students’ preferred advising style, and their satisfaction with academic advising. The survey was based on responses gathered from 111 undergraduates from the School of Engineering, UiTM Pulau Pinang. The Academic Advising Inventory (AAI) by Winston and Sandor (2002) was used to assess the advising method in UiTM Pulau Pinang. The results showed that 83.8% students identified their current academic advisor as using a developmental advising style and 72.1% respondents preferred developmental advising. Meanwhile, 97.3% students were satisfied with the academic advising that they received in UiTM Pulau Pinang. In addition, the students who had created a positive relationship with their assigned academic advisor reported having more satisfaction with their education experience and positively developed as a student.